Editorial: Rethinking social cohesion and its relationship to exclusion - Kiguwa, Peace; Langa, Malose (PINS-Psychology in Society, 2024)
Since the March 2015 call for this special issue several key events have taken place in the country that belie the state’s utopian vision of a supposed non-racial and socially cohesive South Africa. The growing sense of discord with this vision of cohesion has been evident in movements across the country such as Rhodes Must Fall, Open Stellenbosch Collective (OSC), Black Student Movement (Rhodes), and Fees Must Fall movement. 2015 also saw the upsurge of xenophobic violence across the country, anxieties over the country’s economic future that translated into the recent and contentious Zuma Must Fall march. Service delivery protests across the country continue to highlight the sense of impatience for a better life. These events cannot be understood or discussed in isolation from the country’s broader structural, socioeconomic and socio-history. Add to this the increasing ‘race wars’ currently being played out in the public domain of social media and increasing service delivery protests across the country. No doubt about it: South Africa remains racially and economically divisive in ways that make it impossible to imagine the possibilities for building “cohesion at the same time that we recognize, protect and give expression to difference” (Department of Arts and Culture, Social cohesion and social justice in SA, 2012 report, p 13).